2021
DOI: 10.1128/spectrum.00526-21
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genomic Diversity and Antimicrobial Susceptibility of Bifidobacterium pseudocatenulatum in a Vietnamese Population

Abstract: Bifidobacterium pseudocatenulatum is a beneficial member of the human gut microbiota. The organism can modulate inflammation and has probiotic potential, but its characteristics are largely strain dependent and associated with distinct genomic and biochemical features.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
2
5
0
Order By: Relevance
“…Similarly, using arbitrarily primed PCR, Komiya and colleagues showed that identical F. nucleatum strains were isolated from 6/14 paired gut tissue-saliva samples 45 , but WGS was not conducted to verify the exact genetic differences. The populations of Fusobacterium colonising the oral cavity and gut were heterogeneous within some individuals, even at the subspecies level, which mirrors the diversity observed previously for gut commensals such as Bifidobacterium 46 . Chronic infections with Helicobacter pylori at the stomach, which increases the risk of gastric cancer, usually result in extensive clonal propagations detected by WGS within each patient, though isolates were collected in a single timepoint 47 .…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, using arbitrarily primed PCR, Komiya and colleagues showed that identical F. nucleatum strains were isolated from 6/14 paired gut tissue-saliva samples 45 , but WGS was not conducted to verify the exact genetic differences. The populations of Fusobacterium colonising the oral cavity and gut were heterogeneous within some individuals, even at the subspecies level, which mirrors the diversity observed previously for gut commensals such as Bifidobacterium 46 . Chronic infections with Helicobacter pylori at the stomach, which increases the risk of gastric cancer, usually result in extensive clonal propagations detected by WGS within each patient, though isolates were collected in a single timepoint 47 .…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, our approach allows for delineation of bacteria from tumour and non-tumour sites, which is inaccessible by faecal metagenomes. The populations of Fusobacterium colonizing the oral cavity and gut mucosa were heterogeneous within each individual, even at the subspecies level, which mirrors the diversity observed previously for gut commensals such as Bifidobacterium species [47]. Though this study did not provide evidence of genetic relatedness between oral and gut Fusobacterium isolates, this likely point to the high diversity of Fusobacterium in the oral niche [48].…”
Section: Discussionsupporting
confidence: 71%
“…Representatives of these genera are known to be early and long-term persistent colonizers of infant intestine that can, in some settings, promote inflammatory response (53). By contrast, several inflammation-reducing representatives of the Bifidobacterium genus, from the early human milk oligosaccharide-metabolizer B. longum to the later complex carbohydrate relying B. pseudocatenulatum (54), commonly associated with weaning to solid food in early age, also showed high relative importance. The involvement of most important taxa in different aspects of inflammatory response resonates with previous findings that associate chronic inflammation with changes to neural responses in some types of stimuli (55).…”
Section: Discussionmentioning
confidence: 99%